Anatomic study of the mandibular foramen, lingula and antilingula in dry mandibles, and its statistical relationship between the true lingula and the antilingula - Monnazzi, M. S.; Passeri, L. A.; Gabrielli, Mário Francisco Real [UNESP]; Bolini, Paulo Domingos André [UNESP]; de Carvalho, W. R. S. [UNESP]; da Costa Machado, H. (Churchill Livingstone, 2012)
The authors verified the anatomical location of the mandibular foramen, lingula and antilingula in dry mandibles, aiming to obtain information that could be used when performing mandibular osteotomies. Forty-four mandibles (88 sides) were evaluated. The distances were measured using a sliding calliper, with the mandibles fixed in a reproducible position. Results showed that the mandibular foramen is on average 5.82 mm below the lingula. Regarding the statistical comparison between the mandibular foramen entrance and the anti lingula position, there is no correlation between the position of those two structures in the studied sample. The mandibular foramen is slightly posterior in relation to the centre of the ramus. The lingula is an important anatomic landmark for ramus surgery, and for determining the distance to the mandibular foramen entrance. The use of the antilingula as a landmark for the position of the vertical ramus osteotomy is not recommended.
Keywords: anatomy; foramen; lingual; antilingula; mandible